1987
DOI: 10.1007/bf00383848
|View full text |Cite
|
Sign up to set email alerts
|

Changes in psychiatric symptoms related to EEG and cerebral blood flow following electroconvulsive therapy in depression

Abstract: Changes in psychiatric symptoms following electroconvulsive therapy (ECT) were related to alterations in global EEG and cerebral blood flow (CBF) in 21 in-patients suffering from depression. They were examined by clinical ratings, EEG, and CBF immediately before and 1 to 3 h after treatments during an ECT series and at follow-up. Four symptom clusters from a factor analysis of symptoms in depression, representing different dimensions of emotion, cognition, and psychomotor retardation, were used for clinical de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…The high remission rate (95%) after ECT in psychotic depressed patients as compared with depressed patients without psychotic features (83%) supports the argument that psychotic depression is a distinguishable nosological entity [ 24 ]. The EEG characteristics reported in our study agree in general with earlier reports [ 25 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…The high remission rate (95%) after ECT in psychotic depressed patients as compared with depressed patients without psychotic features (83%) supports the argument that psychotic depression is a distinguishable nosological entity [ 24 ]. The EEG characteristics reported in our study agree in general with earlier reports [ 25 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, this study also showed that only clinical ratings more focused on PMD than the Hamilton depression ratings scale (HDRS) predicted P300 latency. In a group of patients receiving electroconvulsive treatment, clinical ratings of PMD were positively correlated with frequency decreases during initial improvement, whereas the reverse relationship was found during the later partial remission phase ( 32 ). One study by Nieber et al ( 33 ) showed a positive correlation between decreased frequencies in particular regions of the theta and alpha (7–13 Hz) spectrum and overall retardation, with motor retardation, in particular.…”
Section: Electroencephalographymentioning
confidence: 96%
“…The emergence of rebound SWA is not limited to pharmacological agents that possess antidepressant properties. Postictal increases in SWA after ECT are widely documented, and other convulsive therapies, such as flurothyl, share similar features (Chusid and Pacella, 1952;Fink and Kahn, 1957;Chatrian and Petersen, 1960;Kriss et al, 1978;Silfverskiöld et al, 1987;Sackeim et al, 1996;Perera et al, 2004). Notably, pronounced postictal EEG slowing has been associated with rapid antidepressant responses (Folkerts, 1996) and clinical improvement after ECT (Nobler et al, 1993;Suppes et al, 1996).…”
Section: Sleep and Rapid Antidepressant Effectsmentioning
confidence: 99%